The effect of microvascular obstruction on the myocardial microstructure: a diffusion tensor imaging study. (8th February 2021) - Das, A; Kelly, K; Aldred, M; Teh, I; Stoeck, CK; Kozerke, S; Chowdhary, A; Craven, T; Jex, N; Ben-Arzi, H; Thirunavukarasu, S; Greenwood, JP; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): Heart Research UK Background: Diffusion tensor cardiac magnetic resonance (DT-CMR) imaging allows for characterising myocardial microstructure in-vivo using mean diffusivity (MD), fractional anisotropy (FA), secondary eigenvector angle (E2A) and helix angle (HA) maps. Following myocardial infarction (MI), alterations in MD, FA and HA proportions have previously been reported. E2A depicts the contractile state of myocardial sheetlets, however the behaviour of E2A in infarct segments, and all DTI markers in areas of microvascular obstruction (MVO) is also not fully understood.  Purpose: We performed spin echo DTI in patients following ST-elevation MI (STEMI) in order to investigate acute changes in DTI parameters in remote and infarct segments both with and without MVO. Method: Twenty STEMI patients (16 men, 4 women, mean age 59) had acute (5 ± 2d) 3T CMR scans. CMR protocol included: second order motion compensated (M012) free-breathing spin echo DTI (3 slices, 18 diffusion directions at b-values 100s/mm2[3], 200s/mm2[3] and 500s/mm2[12], reconstructed resolution was 1.66x1.66x8mm); cine and late gadolinium enhancement (LGE) imaging. Average MD, FA, E2A HA parameters were calculated on a  16 AHA segmental level. HA maps were described by dividing values into left-handed HA (LHM, -90° < HA < -30°), circumferential HA (CM, -30° < HA < 30°), and right-handed HA (RHM, 30° < HA < 90°) and reported as relative proportions. Segments were defined as infarct (positive for LGE) and remote (opposite to the infarct).  Results: DTI acquisition was successful in all patients (acquisition time 13 ± 5mins). Ten patients had evidence of MVO on LGE images. MD was significantly higher in infarct regions in comparison to remote; MVO-ve infarct segments had significantly higher MD than MVO + ve infarct segments (MD remote= 1.46 ± 0.12x10-3mm2/s, MD MVO + ve = 1.59 ± 0.12x10-3mm2/s, MD MVO-ve  = 1.75 ± 0.12x10-3mm2/s, ANOVA p < 0.01). FA was reduced in infarct segments in comparison to remote; MVO-ve infarct segments had significantly lower FA than MVO + ve infarct segments (FAremote= 0.37 ± 0.02, FA MVO + ve = 0.31 ± 0.02 x 10-3mm2/s, MD MVO-ve =0.25 ± 0.02, ANOVA p < 0.01). E2A values were significantly lower in infarct segments compared to remote; MVO + ve infarct segments had significantly lower values than MVO-ve. (E2A remote= 57.4 ± 5.2°,  E2A MVO-ve = 46.8 ± 2.5°,  E2A MVO + ve = 36.8 ± 3.1°, ANOVA p < 0.001). RHM% (corresponding to subendocardium) was significantly lower in infarct segments compared to remote; MVO + ve infarct segments had significantly lower RHM% than MVO-ve. (RHM remote= 37 ± 3%, RHM RHM MVO-ve= 28 ± 7%,  MVO + ve= 8 ± 5%, ANOVA p < 0.001). Conclusion: The presence of MVO results in a decrease in MD and increase in FA in comparison to surrounding infarct segments. However, the reduction in E2A and right-handed myocytes on HA in infarct segments is further exacerbated by the presence of MVO. Further study is required to investigate the underlying mechanisms for such alterations in signal intensity.